Near-fatal asthma: Clinical and physiologic features, perception of bronchoconstriction, and psychologic profile - Boulet, Louis-Philippe; Deschesnes, Francine; Turcotte, Hélène; Gignac, François (Journal of allergy and clinical immunology, 1991)
We studied 19 subjects with asthma (11 men and eight women, aged 20 to 66 years), 6 months to 5 years after a near-fatal (NF) episode of asthma (NF group). Mean duration of asthma was 16.3 ± 2.4 years. On reevaluation, all subjects were using an inhaled β 2-agonist and inhaled steroids (mean daily dose of budesonide, 1070 μg [N = 5], and beclomethasone, 1079 μg [N = 14]). Two subjects were taking prednisone, 10 and 15 mg/day. Subjects were matched for age, sex, atopic status, baseline FEV 1, and medication use to a control group (C group) of subjects with asthma who had never experienced an NF asthma episode. All subjects had the following evaluation: (1) questionnaire on the characteristics of their asthma, (2) spirometry, (3) morning and evening measurements of peak expiratory flow rates (PEFR) with daily recordings of asthma symptoms for 4 weeks, and (4) psychometric evaluation with the Minnesota Multiphasic Personality Inventory. Ten subjects of the NF group and 13 of the C group had a methacholine challenge with scoring of dyspnea on a modified Borg scale. Mean percent predicted (±SEM), FEV 1, FVC, and PEFR were similar for the NF and C groups with respective values of 63.4 (4.4), 61.3 (5.6), 81.1 (4.5), 79.1 (3.8), 61.3 (5.6), and 62.4 (6.1). Geometric mean of the provocative concentration of methacholine causing a 20% drop in FEV 1 (milligrams per milliliter) was 0.61 for the NF group (N = 10) and 1.18 for the C group (N = 13). In comparison to the C group, subjects of the NF group had an increased diurnal variations of PEFR ( p ≤ 0.0002), and more subjects had poor asthma control (NF = 13; C = 5) or a poor treatment compliance (NF = 11; C = 4). No particular psychologic profile could be found on analysis of the Minnesota Multiphasic Personality Inventory in either group. However, analysis of individual profiles revealed more frequent personality disturbances with reduced adaptative personality characteristics in the NF group than in the C group. In conclusion, subjects with asthma who experienced NF asthma have (1) increased diurnal variations of PEFR, (2) an increased prevalence of poorly controlled asthma and reduced compliance to treatment, and (3) less adaptative personality characteristics and more psychologic disturbances that can affect asthma control. However, they do not differ significantly from a C group for perception of dyspnea.